The Upheaval of Takhrij Hadith Initiators and Their Offers of Its Methods, Between Aḥmad al-Ghumārī and Maḥmūd al-Ṭaḥḥān - Aennul Yaqin (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2022)
Books on takhrij hadith have appeared since the 6th century AH. In that century, people had no difficulty finding a hadith, because of their high level of knowledge and memorization. However, over time, hadith was cultivated not only by hadith experts, but also the general public. They have difficulties in searching for hadiths, especially since the previous figures did not inherit the steps of searching for hadiths. It was only in the 14th century AH, that there were figures who had concern for this problem. Experts are divided into two camps in determining who was the pioneer of the takhrij hadith method. Some say Maḥmūd al-Ṭaḥḥān, some others say Aḥmad al-Ghumārī. In this article, we discuss the pioneering debate on the takhrij hadith method. The research method used is inductive-comparative with the main references, namely the books Ḥuṣūl al-Tafrīj and Uṣūl al-Takhrīj. Apart from that, this article also discusses the takhrij hadith method which is offered by both of them. The results of this article indicate that the pioneer of the takhrij hadith method was Aḥmad al-Ghumārī, although Maḥmūd al-Ṭaḥḥān claims he has not found any figures who have written about the takhrij hadith method. As for their offer of the takhrij method, Aḥmad al-Ghumārī presents his offer in two ways, while Maḥmūd al-Ṭaḥḥān presents it in five ways.